PENGARUH KOMBINASI SANTAN DAN GULA KELAPA TERHADAP KUALITAS ES KRIM SUSU KEDELAI - Budianta, Tarsisius Dwi Wibawa; Soepardi, H. Goeswono; Yuliana, Yuliana (Jurnal Teknologi Pangan dan Gizi, 2003)
The aim of this research was to investigate the effect of utilization of coconut milk and coconut sugar in soybean milk ice cream production on chemical, physical and sensory properties of ice cream. Six combination of coconut milk and coconut sugar proportion (9:25; 11:23; 13:21; 15:19; 17:17; and 19:15) were formulated in soybean milk ice cream production. The quality parameters including chemical composition, overrun, delatation rate and flavor were measured. It was found that combinaton of coconut milk and coconut sugar proportion affected and quality parameters. The combination of 9% coconut milk and 25% coconut sugar resulted in the best soybean milk ice cream. The chemical composition of this ice cream : fat 3.00%, protein 3.88%, total sugar 15.30% and total solid 24.42%. This ice cream had 50.36% of overrun and 0.2548 g/min of delatation rate and were prefered by the consumer panelist.